1993
DOI: 10.1002/jcc.540140205
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and semimicroscopic calculations of electrostatic energies in proteins by the POLARIS and ENZYMIX programs

Abstract: Different microscopic and semimicroscopic approaches for calculations of electrostatic energies in macromolecules are examined. This includes the Protein Dipoles Langevin Dipoles (PDLD) method, the semimicroscopic PDLD (PDLD/S) method, and a free energy perturbation (FEP) method. The incorporation of these approaches in the POLARIS and ENZYME modules of the MOLARIS package is described in detail. The PDLD electrostatic calculations are augmented by estimates of the relevant hydrophobic and steric contributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
815
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 464 publications
(817 citation statements)
references
References 73 publications
2
815
0
Order By: Relevance
“…The starting point for our calculations was the high--resolution (1.6 Å) X--ray structure of MAO B in complex with 2--(2--benzofuranyl)--2--imidazoline), 13 pK a calculations were performed using the semi--macroscopic protein dipole / Langevin dipole approach of Warshel and coworkers, in its linear response approximation version (PDLD/S--LRA), 49,[54][55][56] To parameterize the charge distribution of oxidized FAD and dopamine, electrostatic potential derived atomic charges were obtained on the optimized structures at the (PCM)/B3LYP/6-31G(d) level of theory in conjunction with the UFF radii as implemented in Gaussian09 program. 57 The essence of the PDLD/LRA pK a calculation is to convert the problem of evaluating a pK a in a protein to evaluation of the change in "solvation" energy associated with moving the charge from water to the protein.…”
Section: Methodsmentioning
confidence: 99%
“…The starting point for our calculations was the high--resolution (1.6 Å) X--ray structure of MAO B in complex with 2--(2--benzofuranyl)--2--imidazoline), 13 pK a calculations were performed using the semi--macroscopic protein dipole / Langevin dipole approach of Warshel and coworkers, in its linear response approximation version (PDLD/S--LRA), 49,[54][55][56] To parameterize the charge distribution of oxidized FAD and dopamine, electrostatic potential derived atomic charges were obtained on the optimized structures at the (PCM)/B3LYP/6-31G(d) level of theory in conjunction with the UFF radii as implemented in Gaussian09 program. 57 The essence of the PDLD/LRA pK a calculation is to convert the problem of evaluating a pK a in a protein to evaluation of the change in "solvation" energy associated with moving the charge from water to the protein.…”
Section: Methodsmentioning
confidence: 99%
“…All simulations were performed using the MOLARIS simulation package. 50 The nucleic acid bases were represented by AMBER charges 51 and ENZYMIX vdW parameters (after validation that these parameters give reliable solvation energies and base-pairing energies and structures). A single center model with the vdW parameters r* = 1.30 and ε = 0.06 kcal/mol 13 was used for the Mg 2+ ions.…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding binding energies are obtained by following the same strategy used in our recent study, where we reproduced the observed change in TS binding free energy in different mutants and upon changing the base (Rucker et al 2009). In this approach, we evaluated the binding energy of the chemical (triphosphate) and the base sites separately, by running independent Protein Dipole/Langevin Dipole simulations (PDLD/S) using the LRA version (Lee et al 1993 ;Sham et al 2000), and using dielectric constants of 40 and 2 for the chemical (triphosphate) and base sites, respectively (the justification for this approach is presented in Rucker et al 2009). The corresponding calculated binding free energies reproduced the balance between the binding of the base and the chemical sites, which is the essence of the allosteric effect that controls the fidelity of DNA polymerases.…”
Section: Exploring the Molecular Basis For The Observed Fidelitymentioning
confidence: 99%